Effect of hotel employees' workplace friendship on workplace deviance behaviour: Moderating role of organisational identification. (July 2020) - Zhuang, Wen-Long; Chen, Kuan-Yang; Chang, Chia-Lin; Guan, Xinhua; Huan, Tzung-Cheng
Highlights: Workplace friendship (WF) negatively affects the workplace deviance behaviour (WDB) of hotel employees. Organisational identity (OI) moderates the relationship between WF and WDB of the hotel employees. WF includes friendship opportunities and friendship prevalence. WDB includes production deviance, political deviance, property deviance, and personal aggression. Abstract: This study aims to explore the effect of friendships at workplaces (including friendship opportunities and friendship prevalence) on the workplace deviance behaviour (including production deviance, political deviance, property deviance, and personal aggression). This study included an examination of organisational identification for moderating relationships. The surveyees were employees and supervisors in five-star hotels in Taiwan who were willing to cooperate with the survey; each supervisor managed ten employees. A purposive sampling method, a non-probability sampling method, was employed. A total of 600 employee questionnaires were distributed, and the number of valid questionnaires was 357. The results reveal the following: (1) the friendship opportunities and friendship prevalence of hotel employees negatively influenced production deviance and (2) friendship prevalence of hotel employees negatively influenced political deviance, property deviance, and personal aggression. Moreover, organisational identification moderates the relationship between hotel employees' workplace friendship and deviance behaviour. Management implications and follow-up suggestions are proposed based on the study results.